Hydrothermal Generation of Conjugated Polymers Using the Example of Pyrrone Polymers and Polybenzimidazoles - Taublaender, M. Josef (Angew Chem Int Ed Engl, 2020)
Various polyimides and polyamides have recently been prepared via hydrothermal synthesis in nothing but H(2)O under high‐pressure and high‐temperature conditions. However, none of the prepared polymers feature a truly conjugated polymer backbone. Here, we report on an expansion of the synthetic scope of this straightforward and inherently environmentally friendly polymerization technique to the generation of conjugated polymers. Selected representatives of two different polymer classes, pyrrone polymers and polybenzimidazoles, were generated hydrothermally. We present a mechanistic discussion of the polymer formation process as well as an electrochemical characterization of the most promising product.